Kegiatan Penapisan Pemeriksaan Kadar Asam Urat terhadap Hiperurisemia pada Populasi Lanjut Usia - Sari, Triyana; Lumintang, Valentino Gilbert; Sukianto, Louise Audrey; Edbert, Bruce; Gunaidi, Farell Christian; Santoso, Alexander Halim (Jurnal Pengabdian Masyarakat, 2024)
Hyperuricemia, characterized by increased serum uric acid levels, occurs due to an imbalance between uric acid production and excretion. The prevalence in adults and the elderly in China is 12.69% and is higher in men (17.7%) than women (8.5%). Contributing factors such as genetics, diet, and lifestyle changes, lead to an increased risk of gout, kidney stones, and cardiovascular disease. Chronic hyperuricemia can cause joint damage and deformity due to the deposition of urate crystals. This activity uses the PDCA (Plan-Do-Check-Action) methodology to screen for hyperuricemia in the elderly at St. Mary's Church. Francis of Assisi. The screening results showed that 12 people (33.33%) of the 36 participants had hyperuricemia. Early detection of hyperuricemia is very important in preventing complications such as gout and cardiovascular disease. Regular check-ups and lifestyle changes can significantly improve health outcomes and quality of life for seniors.